Profil Hasil Belajar Matematika Peserta Didik Sekolah Dasar - Supriyadi, Supriyadi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2021)
This research aims to describe the profile of mathematics learning outcomes of class II students at Kedungwinangun State Elementary School. This research is a qualitative descriptive research. The participants in this research were 25 second grade students at Kedungwinangun State Elementary School 3. Research was collected by observation, interviews and documentation. Data were analyzed using descriptive statistics. The results of the research show that the profile of student learning outcomes in the mathematics subject content of elementary school students is quite good with a percentage of 79% and is influenced by the teacher's ability to teach, students' learning motivation, and the learning methods used by the teacher.